Paul and the philosophers' faith: discourses of pistis in the Graeco-Roman world - Sierksma-Agteres, Suzan (Ancient philosophy & religion, 2024)
The notion of faith experienced a remarkable surge in popularity among early Christians, with Paul as its pioneer. Yet what was the wider cultural significance of the pistis word group? This comprehensive work contextualizes Paul’s faith language within Graeco-Roman cultural discourses, highlighting its semantic multifariousness and philosophical potential. Based on an innovative combination of cognitive linguistics and discourse analysis, it explores ‘faith’ within social, political, religious, ethical, and cognitive contexts. While challenging modern individualist and irrational conceptualizations, this book shows how Paul uses pistis to creatively configure philosophical narratives of his age and propose Christ as its ultimate embodiment